MARINE ACCIDENT INSURANCE AGREEMENT FOR SHIP PASSENGERS - Mukhti Mukhti (Badan Penerbit STIEPARI Press, 2023)
Legal regulation of accident insurance agreement at sea for ship passengers Article 3 of Law No. 2 of 1992 on insurance business. Implementing the accident insurance agreement at sea for passengers of ships is the implementation of the rights and obligations of the parties to the insurance agreement. Factors that become obstacles to the examination of the accident insurance agreement at sea for passengers on ships are late or inappropriate premium payments, reporting claims that exceed the period due to events that are not guaranteed in the policy, the insured cannot complete the required claim supporting documents, the insured does not file a claim 12 months after the incident, and the insured demands more than specified in the policy. An accident insurance agreement at sea for passengers of ships is the implementation of the rights and obligations of the parties to the insurance agreement. The primary obligation of the insurer in the insurance agreement, especially personal accident insurance, is to compensate losses in the form of compensation, which is the insured's right. However, the obligation to compensate is a conditional obligation for the occurrence or non-occurrence of an agreed event resulting in a loss due to an accident. More stringent legal arrangements are needed in the accident insurance agreement at sea for ship passengers to pay more attention to the principles of the Criminal Procedure Code, which is a simple, fast, and light cost to immediately implement the next stage of the judicial process.